Analisis Profil Pemahaman dan Ketertarikan Mahasiswa Biologi pada STEM Education - Eka Kurniati; Hadi Suwono; Ibrohim Ibrohim (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: STEM Education is currently attracting the attention of many parties including biology students to apply in the classroom. Students' understanding and interest in STEM Education are two basic things to support the successful implementation of STEM Education. Nevertheless, studies on student profiles related to the understanding and interest of STEM Education especially in biology students are still difficult to find. The objectives of this article was to investigate the profile of understanding and interest in STEM, which was analyzed in a descriptive quantitative manner by conducting a survey of 42 masters in biology education. The findings indicate that biology students have basic knowledge of STEM education and a relatively high interest in STEM education. As 79% of prospective educators claim they are interested in studying STEM, and 62% say that it is necessary for teachers to consider STEM. Institution support is deemed necessary to be increased and optimized in order to enhance students' knowledge and readiness in implementing STEM. Abstrak: STEM Education saat ini sedang menarik perhatian banyak pihak termasuk mahasiswa biologi untuk diterapkan di dalam kelas. Pemahaman dan ketertarikan mahasiswa pada STEM Education merupakan dua hal yang mendasar untuk menunjang keberhasilan implementasi STEM Education. Meskipun demikian, studi mengenai profil mahasiswa terkait pemahaman dan ketertarikan STEM Education khususnya pada mahasiswa biologi masih sulit ditemukan. Tujuan dari penelitian ini untuk mengeksplor profil pemahaman dan ketertarikan pada STEM yang dikaji secara deskriptif kuntitatif dengan melakukan survei pada 42 mahasiswa magister Pendidikan Biologi. Hasil menunjukkan bahwa mahsiswa Biologi telah memiliki pengetahuan dasar terkait STEM Education dan memiliki ketertarikan yang relatif tinggi terhadap STEM Education. Sebanyak 79% mahasiswa calon pendidik mengklaim tertarik mendalami STEM dan 62% menyatakan bahwa penting bagi guru untuk memahami STEM. Dukungan instansi dianggap perlu ditingkatkan dan dioptimalkan untuk dapat menambah pengetahuan dan kesiapan mahasiswa dalam mengimplementasikan STEM.